The Influence of Internal Auditor Competence, Audit Technology Readiness, and Organizational Culture on The Speed of Reporting Audit Findings at PLN Medan - Lasson Padang; M. Irsan Nasution`; Renny Maisyarah (Equivalent : Journal of Economic, Accounting and Management, 2026)
This study aims to examine the effects of Internal Auditor Competence, Audit Technology Readiness, and Organizational Culture on the Timeliness of Audit Findings Reporting. The study is grounded in the Resource-Based View (RBV), Institutional Theory, and the COBIT 2019 information technology governance framework to explain the determinants of internal audit process performance. The research was conducted at PT PLN Medan Region. The population of this study consisted of all internal auditors and accounting staff working at PT PLN Medan Region, totaling 50 employees. A census (saturated sampling) technique was applied, whereby all members of the population were included as research respondents. A quantitative research approach was employed using a structured questionnaire. Data quality was assessed through Pearson correlation validity tests and Cronbach's Alpha reliability tests, which indicated that all measurement items were valid and reliable, with Cronbach's Alpha values exceeding 0.60. The data were subsequently analyzed using multiple linear regression, preceded by classical assumption tests, including tests of normality, heteroscedasticity, and multicollinearity. The results of these tests confirmed that the data were normally distributed, free from heteroscedasticity, and exhibited no multicollinearity, indicating that the regression model was appropriate for interpretation. The findings reveal that Internal Auditor Competence and Audit Technology Readiness have a positive and significant effect on the Timeliness of Audit Findings Reporting, whereas Organizational Culture does not have a significant direct effect. Simultaneously, the three independent variables significantly influence the dependent variable, with a coefficient of determination of 63.5%, indicating strong explanatory power of the model. These results highlight that human resource capabilities and audit technology readiness are the primary drivers in accelerating the audit findings reporting cycle, while organizational culture functions as an indirect supporting factor.